Social-hygienic assessment of medical service quality in rural areas of the Tomsk region - S. M. Khlynin; N. V. Zakotnova; I. A. Linok; Ye. N. Obraztsova; L. V. Kapilevich (Бюллетень сибирской медицины)
Results of out-departments expertise revealed that medical service quality in rural areas of theTomskregion is worse than in municipal hospitals. The causes of such discrepancy is non-complete examination and wrong diagnosis. Patients’ assessment of medical service quality is highly controversial: 72% of patients noted improving of treatment results but only 42% of patients considered their treatment results to be satisfactory.The leading factors of supplying quality of medical service in the rural health care are presence of modern diagnostic tools in rural hospitals (9.2–9.7 marks), and increasing of specialists’ quality of work (8.0–9.5 marks). In addition, medical institutions’ chiefs note the role of financial independence of the physician – in-chief (9.5 marks) and medical insurance companies experts note increasing out-departmental control (9.5 marks).